Individuality as the subject of differentialpsychological research - Trukhan, Elena A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes the differential and integral approach to the study of human individuality. It discusses the paradox of individuality as the subject of study of differential psychology. It is concluded that differentiation and integration are necessary mechanisms for transition from the holistic «indivisibility» of the individual to the «individuality» as integrated human uniqueness.
Keywords: individuality; differential psychology; research subject; integration; differentiation